Collaboration of Islamic Religious Teachers with Counseling Guidance Teachers for fostering the morals of Students in Guiding of Students MA NU Banat Kudus - Fanny Nada Fajri; Ashif Az Zafi (Educan : Jurnal Pendidikan Islam, 2021)
Collaboration of Islamic Religious Teachers with Counseling Guidance Teachers in Guiding of Students Islamic high school Banat Kudus for fostering the morals of Students try to collaborate programs to run well in making students into moral human beings , using qualitative descriptive methods, Collaboration of Islamic Religious Teachers with Counseling Guidance Teachers in forming akhlakul karimah students are backgrounded because both have a close relationship with the formation of student morality, it can be seen from the task of both teachers. So this collaboration is more about the division of tasks and roles of each. Islamic Religious Teachers introduce a strategy of planting morals while Counseling Guidance Teachers follow up, maximize, overcome problems related to morality.